Effect of bubbles around an underwater robot arm on thrust during the crawl stroke motion - Nakashima, M.; Karako, Y. (Procedia Engineering, 2014)
The objective of this study was to clarify the effect of bubbles on thrust by means of an underwater robot arm. The underwater robot arm had five degrees-of-freedom (three for the shoulder and two for the elbow) which were actuated by five electric motors. The size was almost the same as human. On the top of the robot, a dynamometer was installed to measure the thrust. The robot arm was mounted in a circulating water tank. Two types of stroke of the crawl, that is, I-shaped and S-shaped, were performed. In order to distribute artificial bubbles around the arm, an elastic porous stick was attached to the arm. The stick was connected to an air compressor. Two attaching positions of the stick, that is, palm side and the back side of the palm, were tested. The following findings were obtained from the experiment: For the I-shaped stroke, the effect of bubbles became significant when the thrust became maximum. The thrust decreased when the porous stick was attached to the back side of the palm. On the other hand, the thrust increased when the stick was attached to the palm side. For the S-shaped stroke, the effect of bubbles exhibited more complicated behavior than for the I-shaped stroke, and clear tendency of the effect could not be seen.